Frequency of Gastrointestinal Nematodes in Cattle in Region in Aceh Province - Zulfikar Zulfikar; Abdul Malik; Afkar Afkar (Animal Husbandry Department, The Faculty of Agriculture, Universitas Syiah Kuala, 2026)
The high presence of nematode worms in cattle has a significant impact on productivity, reducing production value throughout the year, economic losses, meat sufficiency, and endangering food security as a source of animal protein. The increasing prevalence of gastrointestinal nematodes is influenced by environmental ecological conditions and maintenance management. This study was conducted in North Aceh Regency (lowlands <100 masl) and Gayo Lues Regency (highlands >800 masl), from September to October 2025. The samples used were cow feces, categorized by age group and sex, through the interaction of the physical environment (topography, temperature, humidity, rainfall, and soil pH). The sample size for each region was 90 cows. The identification of gastrointestinal nematode eggs in cow feces was carried out at the Mathematics and Natural Sciences Laboratory of Almuslim University. The prevalence of gastrointestinal nematodes in cattle was higher in the lowlands than in the highlands, showing a significant difference (P<0.01). The frequency of gastrointestinal nematodes based on the sex of cattle in the lowlands was significantly (P<0.05) and highlands did not differ significantly (P>0.05). Furthermore, the presence of gastrointestinal nematodes in cattle is related to environmental factors. Topography, temperature, and humidity significantly influenced the two regions (P<0.01), with a higher prevalence in the lowlands. It can be concluded that environmental factors vary significantly across regions, significantly influencing the increase in gastrointestinal nematode infestation in cattle in the region. The future context for cattle farming and disease management, particularly regarding the presence of helminth parasites, requires appropriate and sustainable models.